1233PLandscape of PD-L1 expression status in Chinese solid tumour patients. (1st October 2019) - Zhong, Y; Zhou, Y; Bai, Y; Zhang, B; Zhang, Y
Abstract: Background: PD-L1 expression was approved by U.S. FDA as companion or complementary diagnostic for most anti-PD-1/ PD-L1 inhibitors, which is well accepted as one of the important biomarkers in the selection of patients who would have high potential to respond. By far, the PD-L1 prevalence in Chinese solid tumor patients is poorly reported. In lung cancer, the correlation between PD-L1 expression and another important biomarker tumor mutation burden (TMB) has been demonstrated to be weak, however, the results in other types of solid tumor are still limited, which needs further explorations. Methods: A total of 6, 571 Chinese solid tumor patients, including 1, 534 lung cancer patients and 5, 037 other solid tumor patients, from 70 sites were studied. The tissue samples, either surgical resection specimens or biopsy samples, were both stained by clinical validated PD-L1 IHC assay and performed the next generation sequencing (NGS) using a validated commercial 381-cancer-gene panel, with panel size over 0.5 MB. TMB was calculated according to NGS results. Results: 835 of 1534 (54.4%) lung cancer patients had PD-L1 expression >1% on tumor cells. The PD-L1 prevalence in NSCLC, small cell lung cancer, squamous cell carcinoma, adenocarcinoma and adenosine squamous cell carcinoma were 55.4%, 16.1%, 64.2%, 52.7% and 66.7%, respectively. Among 5, 037 non-lung solid tumor patients, the proportion of PD-L1 expression >1% is 28.4%, 23.5%, 38.9%, 29.5%, 60% and 37.1% in gastric cancer, colorectal cancer, hepatobiliary cancer, urologic cancer, head and neck cancer and gynecological cancer. The average TMB of PD-L1 expression >1% solid tumor patients (excluding lung cancer) was 10.87/ MB, which is statistically significant higher than PD-L1 expression <1% subgroup (8.64/MB, p = 2.5e-06). Conclusions: The PD-L1 prevalence varied in different tumor type subgroups. And TMB was significant different between PD-L1 expression >1% and <1% subgroups. But, the correlation between PD-L1 and TMB needs more studies, which is important to reveal whether these two biomarkers are mutually independent. Legal entity responsible for the study: 3D Medicine, Shanghai. Funding: 3D Medicine, Shanghai. Disclosure: All authors have declared no conflicts of interest.